Introduction: A research agenda for environmental policy analysis - past, present, and future - Jörgens, H.; Knill, C.; Steinebach, Y. (Routledge handbook of environmental policy, 2023)
This chapter provides a state-of-the-art review of research on environmental policy and governance. Since the 1960s, environmental policy has become a central topic of national and international policy-making. Today, environmental policy is among the most important, and certainly most dynamic, policy domains, with a wide range of topics and subfields such as biodiversity conservation, air pollution control, water protection, waste management, and, above all, the fight against climate change and the transition towards a carbon-free economy. The resulting compendium is a go-to guide for established and newly interested researchers, for students, as well as for governments and policy-making entities. It presents theoretical, conceptual, and empirical developments that have been made in recent years and highlights emerging areas where new research and reflection are warranted.